Judgmental Care Contexts in Emergency Departments: A Qualitative Study in Iran - Alireza Abdi; Shamsodin Rahmani; Mahmoud Rahmati (Journal of Holistic Nursing and Midwifery)
Introduction: Providing non-judgmental care (NJC) is a professional and ethical obligation for nurses. Objective: This study aimed to explore the contexts of judgmental care (JC) in emergency departments (EDs). Materials and Methods: This is a qualitative study using the descriptive phenomenological approach. Participants were 14 nurses working in the EDs of selected hospitals in Kermanshah, Iran, who were selected using a purposive sampling method. Data were collected through in-depth interviews. After recording and transcribing the interviews, the data were analyzed using Colaizzi’s approach. Results: After data analysis, three main themes emerged: Individual characteristics of nurses, social perceptions of nurses and stimulating organization of JC. For the first theme, the sub-themes were “profiteering”, “a justification for underwork”, “difficulty in refraining from judging”, “personal biases”, “nurses’ understanding of their value system”, “personal point of view”, “an action to punish the patient” and “understanding the importance of care”. For the second theme, the sub-themes were “nurse’s perceptions of the patient’s social benefits”, “stereotyping”, “fear of harm”, and “patients’ ignorance of their rights”. For the last theme, the sub-themes were “organizational factors” and “a caring atmosphere in the work environment”. Conclusion: Several facilitating and inhibiting factors related to nurses, patients and the organization can affect JC in the EDs.